2014
DOI: 10.1136/bmjopen-2013-004427
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism ofNFKB1andNFKBIAgenes and liver cancer risk: a nested case–control study in Shanghai, China

Abstract: ObjectivesGenetic variations of nuclear factor-κB (NF-κB) signalling pathway were found to be associated with inflammatory diseases and several malignancies. However, little is known about NF-κB pathway gene polymorphisms and susceptibility of liver cancer. The aim of this study was to investigate whether genetic variants of NFKB1 and NFKBIA were associated with risk of liver cancer in a Chinese population.DesignThe study was designed as a nested case–control study within two prospective cohorts (the Shanghai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Treatment of PLC/PRF/5 hepatoma cells with 500 µmol/l NaHS for 24 h markedly diminished cell apoptosis, and decreased the expression level of caspase-3, an apoptotic factor. The above result was consistent with previous reports (13)(14)(15)(16)(17)(18)(19)). These results demonstrate that H 2 S induces cell proliferation via exerting its dual cytoprotective and anti-apoptosis effects.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Treatment of PLC/PRF/5 hepatoma cells with 500 µmol/l NaHS for 24 h markedly diminished cell apoptosis, and decreased the expression level of caspase-3, an apoptotic factor. The above result was consistent with previous reports (13)(14)(15)(16)(17)(18)(19)). These results demonstrate that H 2 S induces cell proliferation via exerting its dual cytoprotective and anti-apoptosis effects.…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that NF-κB can be activated by various stimuli both in normal cells (13) and in cancer cells (13)(14)(15)(16)(17)(18)(19). Herein, we found that NaHS not only activated NF-κB in PLC/ PRF/5 hepatoma cells, leading to increased phosphorylation of NF-κB p65 and IκBα, but also increased NF-κB nuclear translocation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…is decreased in liver cancer tissue compared with control tissue, and that negative NFKBIA expression predicted poor prognosis in patients with primary HCC (48). A nested case-control study in Shanghai (China) suggested that genetic variants of NFKB1 influenced liver cancer-susceptibility in the Chinese population (49). SOCS2 has been reported to inhibit tumor metastasis (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have tested the association between different forms of cancer and functional variants of genes responsible for the inflammatory process [ 5 – 8 ], such as interleukin 1A ( IL1A ), interleukin 4 ( IL4 ), nuclear factor kappa B1 ( NFKB1 ) and protease-activated receptor 1 ( PAR1 ) [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%